Acute perforated duodenal ulcer is not associated with Helicobacter pylori infection. - Reinbach, D H (1993)
Most patients with chronic duodenal ulcer disease have Helicobacter pylori infection and eradicating it considerably reduces the relapse rate. The prevalence of H pylori in 80 patients (mean age = 52 years, range 17-85) presenting with acute perforated duodenal ulcer was examined and compared with age and sex matched hospital control patients. H pylori state was assessed by serum anti-H pylori IgG (Helico-G kit, Porton) using a titre of 18 or less as negative with a specificity of 89% and sensitivity of 88%. Only 47% of the perforated duodenal ulcer patients were positive for H pylori and this was similar to the value of 50% in the controls. In 51 of the perforated duodenal ulcer patients 14C-urea breath tests were also performed 4-10 weeks after surgery and this confirmed that only 49% were positive for H pylori. None of these patients had received perioperative drugs that might have eradicated the infection. The H pylori positive and H pylori negative perforated duodenal ulcer patients were similar with respect to age (53, 51), smoking (84%, 83%), and consumption of more than 15 units of alcohol per week (42%, 38%). Duodenal ulcer disease had been diagnosed before acute perforation in only 24% of those with H pylori and also 24% of those without the infection. Regular non-steroidal anti-inflammatory drug (NSAID) use was common in both those with (44%) and without (45%) H pylori. In conclusion, the lack of association of acute perforated duodenal ulcer and H pylori infection suggests that perforated duodenal ulcer has a different pathogenesis from chronic duodenal ulcer disease, and that the first should not be regarded simply as a complication of the second.